IMPLEMENTING PROJECT BASED LEARNING MODEL TO IMPROVE STUDENTS’ CREATIVE THINKING ABILITY IN WATER CYCLE (HYDROLOGY) MATERIAL AT GRADE V ELEMENTARY SCHOOL - Feggy Nazua; Nur Aisyah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to analyze to what extend project based learning model improved the students’ creative thinking skills in the water cycle material at grade V SDN Sukanagara. The method of this study was a quasi-experimental method, with Nonequivalent Control Group Design. Samples in this study were 30 students in class VA as the experimental class and 30 students in class VB as the control class. The results showed that there were differences in the ability to think creatively based on the assessment data of the essay test between students who learned through Project Based Learning model and students who learned through direct learning model. This was evidenced from the results of the normality test, homogeneity and t-test, namely the sig value = 0.002 with dk = n1 -1 or dk = 30 - 1 = 29, α = 0.05 meaning that 0.002 < 0.05. Then, H0 was rejected, Ha was accepted. There were differences in the ability to think creatively based on product assessment data between students who learned through Project Based Learning model and students who learned through direct learning model. This was evidenced from the results of the normality test, homogeneity and t-test, namely the sig value = 0.046 with dk = n1 -1 or dk = 30 - 1 = 29, α = 0.05 meaning that 0.046 < 0.05. Then, H0 was rejected, Ha was accepted.